NET-EN treatment leads to delayed HSV-2 infection, enhanced mucin and T cell functions in the female genital tract when compared to DMPA in a preclinical mouse model - Mian, M. Firoz; Pa, Sidney; Rahman, Nuzhat; Gillgrass, Amy; Kaushic, Charu (Frontiers in Immunology, 2024)
Depot-medroxyprogesterone acetate (DMPA) and Norethisterone Enanthate (NET-EN) are progestin-only injectable contraceptives widely used by women in sub-Sharan Africa, where incidence of HIV-1 and HSV-2 infection remains high. Studies indicate that DMPA usage can increase the risk of HSV-2 infection, but limited data indicate no increased risk with use of NET-EN. We therefore investigated the effects of NET-EN and DMPA on susceptibility to vaginal HSV-2 infection in ovariectomized (OVX) mice and effects on immune responses, particularly in the vaginal tract (VT). OVX mice, when treated with NET-EN and infected intravaginally, had delayed genital pathology, decreased viral shedding, and extended survival compared to DMPA- or untreated OVX mice. CD4+ T cells isolated from VT showed no significant change in frequency with either contraceptive. However, DMPA significantly decreased the total number of VT CD4+ and CD8+ T cells and the number of IFN-γ producing CD4 and CD8 T cells and increased the percentage of CD4 and CD8 T cells producing TNF-α compared to untreated mice. In contrast, NET-EN significantly enhanced percentages of CD8+ T cells compared to DMPA treated mice, and frequencies of IFN-γ+ CD4 and CD8 T cells in the VT compared to untreated mice. Comparative analysis of splenic lymphocytes indicated that DMPA treatment resulted in reduction of CD4+ T cell frequency, but enhanced TNF-α+ CD4 T cells compared to untreated mice. NET-EN enhanced the frequency of CD8 T cells, as well as IFN-γ+ and TNF-α+ CD4, and IFN-γ+ CD8 T cells in the spleen compared to untreated mice. Importantly, we found DMPA treatment that significantly reduced mucin production, whereas NET-EN enhanced expression of cell-associated mucin in VT. High levels of mucin in NET-EN mice were associated with lower levels of HSV-2 virus detected in the vaginal tract. This study provides the first evidence that NET-EN treatment can delay HSV-2 infection compared to DMPA.